2021
DOI: 10.3758/s13421-020-01119-0
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between generation constraint and memory

Abstract: Self-generated information is often better remembered than read information (the generation effect). Recent research, however, has shown that generating information under fewer experimental constraints (i.e., fewer limitations on what can be generated) can increase the magnitude of the generation effect. This study systematically varied generation constraint to better understand the effects of constraint on memory. Participants encoded associated cue-target word pairs (above-below) on either the left or right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
3
6
0
Order By: Relevance
“…This finding adds to the literature suggesting that the type of test used in the re-exposure phase has a strong effect on the magnitude of the testing effect in memory (i.e., how much memory improves for tested materials compared to control). Interestingly, our item memory results (improved memory for lower compared to higher constraint test conditions) are consistent with another finding in a different memory domain, the generation effect (Slamecka & Graf, 1978) McCurdy et al, 2021;McCurdy, Viechtbauer, et al, 2020). In particular, this past work on the generation effect has demonstrated that producing materials under lower compared to higher constraint conditions may act to increase relational processing of the cue-target relationship of word pairs, and that this enhanced relational processing leads to improved memory for materials produced in lower compared to higher constraint conditions .…”
Section: Discussionsupporting
confidence: 91%
“…This finding adds to the literature suggesting that the type of test used in the re-exposure phase has a strong effect on the magnitude of the testing effect in memory (i.e., how much memory improves for tested materials compared to control). Interestingly, our item memory results (improved memory for lower compared to higher constraint test conditions) are consistent with another finding in a different memory domain, the generation effect (Slamecka & Graf, 1978) McCurdy et al, 2021;McCurdy, Viechtbauer, et al, 2020). In particular, this past work on the generation effect has demonstrated that producing materials under lower compared to higher constraint conditions may act to increase relational processing of the cue-target relationship of word pairs, and that this enhanced relational processing leads to improved memory for materials produced in lower compared to higher constraint conditions .…”
Section: Discussionsupporting
confidence: 91%
“…At encoding, participants reported "yes" to the pleasantness question on 45% of the trials in the self-reference condition, and 37% of the trials in the other-reference condition, which is consistent with prior work (Leshikar & Duarte, 2012. ), as done before (Bayen et al, 1996;Leshikar & Gutchess, 2015;McCurdy et al, 2017McCurdy et al, , 2019McCurdy et al, , 2021. For both item and context memory, we performed 2 (encoding condition:…”
Section: Resultssupporting
confidence: 78%
“…Overall, although Experiment 2 showed evidence of the relationship between retrieval practice, self-efficacy, and memory, future work should focus on manipulating feedback for both retrieval practice and restudy groups to better understand the effects on self-efficacy on memory under retrieval practice experimental conditions. Overall, finding a relationship between retrieval practice, self-efficacy, and memory, adds to other memory-related work that has the potential to improve memory in educational contexts (Butler & Rodiger, 2007 ; Giannakopoulos et al, 2021 ; McCurdy et al, 2021 ; McCurdy et al, 2019 ; McCurdy et al, in press; McCurdy, Viechtbauer, et al, 2020 ; McDaniel et al, 2007 ). One practical implication of this work is that conditions that give (or imply) negative feedback to students in educational settings may not be motivating, but instead may have the unintended effect of leading to poorer performance on academic tasks.…”
Section: Discussionmentioning
confidence: 54%